PEMBELAJARAN LITERASI DAN NUMERASI PADA PENGALAMAN PROGRAM KAMPUS MENGAJAR ANGKATAN 5 TAHUN 2023 - Kusumadinata, Ali Alamsyah; Qonita H, Annisa (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2023)
Kampus merdeka is a student learning internship program in increasing the capacity of students to become more skilled in social and in working in the community. The purpose of this service is to provide learning to students in providing alternative learning to elementary schools. The implementation method is carried out face-to-face and contributes to activities. The results of the activity show that the independent campus in the literacy and numeracy improvement program provides learning experiences for students and provides increased grades to students. This makes it easier for schools to improve the quality of educational services. In addition, the enrichment of educational models carried out by students in the learning process provides students with the ability to hone their skills and develop intelligent thinking.